Textbook of interventional cardiology
Ideal for cardiologists, surgeons, and referring physicians who need a clinical guide to interventional procedures, Textbook of Interventional Cardiology focuses on the latest treatment protocols for managing heart disorders at every level of complexity. In this updated edition, Dr. Topol continues to bring together experts in the field who present the current state of knowledge and clinical practice in interventional cardiology, including cutting-edge theories, trends, and applications of diagnostic and interventional cardiology, as well as peripheral vascular techniques and practices